Highly permeable hydrophobic nonwoven fabric and method for producing the same

CN119571542BActive Publication Date: 2026-10-30WUXI HONGQING NON WOVEN FABRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411762939.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2026-10-30
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

这种无纺布通过特殊工艺处理,不仅能够保持一定的透气性,还能减少水分子渗透,同时提高空气和水蒸气的流通效果,提升了产品的舒适性和防护性能,然而,目前市面上的此类产品的透气性和疏水性效果的平衡以及生产方法仍有不足之处

Benefits of technology

[0031]本发明的有益效果是:本发明通过PTFE微粉即聚四氟乙烯因其极低的表面能与疏水特性,能够使无纺布在保持高透气性的同时,有效阻挡水分子的侵入,实现透气防水的效果;纳米二氧化硅与聚氨酯树脂的加入,显著提高了无纺布的机械强度和耐久性,使其在保持轻质特性的同时,能够承受更大的物理压力与使用磨损;抗静电剂的添加,减少了材料在使用过程中因摩擦产生的静电积聚;聚酯纤维作为主要成分,提供了无纺布的基础结构与成本优势,同时保证了材料的柔韧性和一定的弹性;通过疏水处理层进一步强化了无纺布的防水性能,在细丝粘合制布之前进行疏水处理,能够加强无纺布疏水性的同时不影响透气性,使高透气性与防水性能并存。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571542B_ABST
    Figure CN119571542B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of textiles, in particular to a high-breathability and hydrophobic non-woven fabric and a production method thereof, which is made of 10-15% PTFE micro powder, 5-10% nano-silicon dioxide, 3-6% polyurethane resin, 1-3% antistatic agent and the rest polyester fiber filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the PTFE micro powder, i.e. polytetrafluoroethylene, can effectively prevent the invasion of water molecules while maintaining high breathability, and realize the effect of breathability and waterproofness, due to its extremely low surface energy and hydrophobic characteristics; the addition of nano-silicon dioxide and polyurethane resin significantly improves the mechanical strength and durability of the non-woven fabric; the hydrophobic treatment layer further strengthens the waterproof performance of the non-woven fabric, and the hydrophobic treatment is performed before the filament bonding process, so that the high breathability and waterproof performance coexist.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile technology, specifically to a highly breathable and hydrophobic nonwoven fabric and its production method. Background Technology

[0002] In the fields of textiles and medical protective equipment, highly breathable and hydrophobic nonwoven fabrics are highly favored due to their unique properties. While traditional nonwoven fabrics possess a certain degree of breathability and water resistance, in practical applications, especially under high humidity or extreme climatic conditions, sanitary nonwoven fabrics often fall short of achieving ideal performance. For example, the hydrophobic properties of conventional nonwoven fabrics gradually decrease after prolonged use, leading to liquid penetration and affecting the product's protective effectiveness. Furthermore, striking a balance between breathability and hydrophobicity is a significant challenge; excessive hydrophobicity often comes at the cost of breathability, which is particularly evident in protective fabrics or outdoor gear that require prolonged wear.

[0003] In recent years, researchers have been dedicated to developing new types of highly breathable and hydrophobic nonwoven fabrics. These nonwoven fabrics, processed with special techniques, not only maintain a certain level of breathability but also reduce water molecule penetration, while simultaneously improving the flow of air and water vapor, thus enhancing the comfort and protective performance of the products. However, the balance between breathability and hydrophobicity in currently available products of this type, as well as their production methods, still have shortcomings. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a highly breathable and hydrophobic nonwoven fabric and its production method.

[0005] The technical solution of this invention is: a highly breathable and hydrophobic nonwoven fabric, comprising, by weight percentage, 10-15% PTFE micro powder, 5-10% nano-silica, 3-6% polyurethane resin, 1-3% antistatic agent, and the balance polyester fiber extruded into filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 10-80 mg / m² on the surface of the filaments. 2 .

[0006] Note: Environmentally friendly materials, including polyester fibers and specific treatment agents, are used to reduce environmental pollution while ensuring product safety and comfort upon human contact. The hydrophobic coating prevents liquid penetration, reduces the chance of microbial growth, and improves the product's hygiene standards.

[0007] The present invention also provides a method for producing the aforementioned high-breathability and hydrophobic nonwoven fabric, comprising the following steps:

[0008] S1, Raw material mixing

[0009] Polyester fiber, PTFE micro powder, nano silica, polyurethane resin and antistatic agent are mixed evenly according to the formula ratio to obtain a mixture.

[0010] S2, Preparation of molten mixture

[0011] The mixture obtained in S1 is fed into a melt extruder, and the temperature is controlled at 220-260℃ to fully melt the PTFE micro powder and obtain a melt mixture.

[0012] S3, Extrusion Modification Treatment

[0013] The molten mixture obtained from S2 was stretched into filaments using an electrospinning device. The filaments were cooled to room temperature and then soaked and washed in deionized water. After drying, the filaments were completely immersed in a lipase solution and stirred for 3–15 hours. Then, they were thoroughly washed with distilled water and dried to obtain modified fibers.

[0014] S4. Preparation of nonwoven fabric

[0015] The modified fibers obtained from S3 are immersed in a hydrophobic dispersion and stirred for 5 to 15 minutes to form a hydrophobic treatment layer on the surface of the modified fibers. After being taken out and dried, a nonwoven fabric with a microporous structure is produced.

[0016] S5, Shaping Process

[0017] The nonwoven fabric described in S4 is subjected to heat setting treatment. The heat setting temperature is controlled at 180-220℃ and the heat setting time is 20-80s to obtain a highly breathable and hydrophobic nonwoven fabric.

[0018] Explanation: Raw materials are mixed according to a specific formula ratio and melted at a precise temperature of 220–260℃ to ensure full reaction of PTFE micropowder, forming a homogeneous molten mixture. This improves the air permeability and hydrophobicity of the nonwoven fabric. Electrospinning technology stretches the molten mixture into fine filaments, and combined with impregnation and reaction with lipase solution, significantly enhancing the hydrophilic and oleophobic properties and structural stability of the fibers, ensuring good morphology during subsequent processing. Modified fibers are immersed in a hydrophobic dispersion, forming a hydrophobic layer on the fiber surface through a chemical reaction, further enhancing the waterproof performance of the nonwoven fabric while maintaining air permeability. Heat setting treatment at a specific temperature and time allows the nonwoven fabric to form a stable microporous structure. The heat setting treatment is carried out within a temperature range of 180–220℃ and a time range of 20–80 seconds, ensuring both the forming effect of the nonwoven fabric and avoiding the degradation of material properties caused by high temperatures, thus ensuring the final quality of the product.

[0019] Furthermore, the antistatic agent mentioned in S1 is antistatic agent ZJ-NW16.

[0020] Description: ZJ-NW16 antistatic agent effectively reduces the surface resistance of nonwoven fabrics, reduces static electricity accumulation, and its excellent antistatic properties improve safety and comfort. A cooling rate of 3–10°C helps to rapidly stabilize the fiber structure, preventing fiber breakage due to uneven shrinkage during cooling and ensuring fiber strength and dimensional stability. A stretch ratio of 1.5–2 times effectively adjusts the molecular arrangement of the fibers, increasing their extensibility and strength while ensuring that the fibers do not suffer structural damage due to excessive stretching. Through precisely controlled cooling and stretching processes, the microporous structure of the fibers is optimized, maintaining high air permeability while ensuring the effectiveness of hydrophobic treatment, thus improving the overall performance of the nonwoven fabric.

[0021] Furthermore, the temperature of the stirring reaction in S3 is controlled at 40–60°C; the cooling rate is 3–10°C; and the stretching ratio is 1.5–2 times.

[0022] Note: Suitable temperature can accelerate the interaction between lipase and other reactants, improve reaction efficiency, thereby shortening processing time and increasing production efficiency. As a protein, the activity of lipase is significantly affected by temperature. The temperature range of 40-60℃ is usually the ideal temperature range for many enzymes to maintain high activity, which can ensure that lipase can effectively catalyze the reaction and improve the hydrophilic and oleophobic properties of the fiber. Excessively high temperature can lead to denaturation and inactivation of biocatalysts such as lipase, and also affect the stability of other raw materials. Controlling the temperature within a suitable range can reduce the risk of thermal degradation and maintain the integrity of raw materials and products. By precisely controlling the temperature of the stirring reaction, the depth and uniformity of fiber surface treatment can be better regulated, thereby obtaining higher quality nonwoven fabric products.

[0023] Furthermore, by mass percentage, the lipase solution described in S3 consists of 0.1–9% Novozym 435, 3–15% ethylene glycol, and the balance being water.

[0024] Note: Lipase Novozym 435 can catalyze a variety of chemical reactions under mild conditions, including esterification, hydrolysis, and transesterification. Ethylene glycol, as a polyol, can act as a cofactor for lipase, helping to regulate the hydrophilicity and solubility of the reaction, thereby affecting the microstructure and surface properties of the fiber. Water, as a solvent, ensures the fluidity of the reaction mixture and the expression of enzyme activity. The content of Novozym 435 in the lipase solution has a direct impact on the reaction rate and conversion rate. An appropriate amount of lipase can ensure sufficient catalytic activity, while excessively high enzyme concentrations can lead to an overcrowded reaction system, affecting enzyme stability and reusability. The addition of ethylene glycol can improve the stability of lipase, especially in organic solvents or non-aqueous phases, helping to maintain the three-dimensional structure of the enzyme and thus its catalytic activity. Water not only acts as a solvent but is also the medium required for lipase activity and also helps to separate the lipase from the reaction products.

[0025] Further, the preparation method of the hydrophobic dispersion described in S4 is as follows: 5-20% calcium carbonate, 10-20% fly ash, 5-15% bentonite, 1-10% silica and the balance fluorinated alkylsilane are ball-milled and mixed, and then water is added to prepare a hydrophobic dispersion with a concentration of 0.1-1 wt% fluorinated alkylsilane.

[0026] Explanation: Fluorinated alkylsilanes possess strong hydrophobicity due to the presence of their fluorine chains, significantly reducing the surface energy of nonwoven fabrics and improving their water-repellent properties. They synergistically work with calcium carbonate, fly ash, bentonite, and silica to form a stable hydrophobic layer, ensuring the performance of the nonwoven fabric in high humidity or water-contact environments. Calcium carbonate and silica, as fillers, enhance the physical strength and abrasion resistance of the nonwoven fabric. The fine particles of fly ash fill the micropores of the nonwoven fabric, improving its density, while the glassy phase component of fly ash helps form a more uniform hydrophobic layer. Through ball milling, the components are uniformly dispersed, resulting in a hydrophobic dispersion that more evenly covers the surface of the nonwoven fabric, optimizing the microporous structure and maintaining good air permeability. The adsorption properties of bentonite can absorb moisture and impurities, improving the chemical stability of the nonwoven fabric and extending its service life.

[0027] Further, in S4, the modified fibers obtained in S3 are divided into two groups at a mass ratio of 1 to 4:1, denoted as modified fiber a and modified fiber b, respectively. Modified fiber a is immersed in a hydrophobic dispersion and stirred for 5 to 15 minutes to form a hydrophobic treatment layer on the surface of the modified fiber. After being taken out and dried, hydrophobic fiber is obtained. Modified fiber b is laid in a crisscross pattern using a multi-channel web laying machine, with each layer of fiber web perpendicular to the previous layer. The number of web layers is 6 to 20. After all layers are laid, the fiber web is bonded together, retaining a portion of the microporous structure and controlling the porosity at 60 to 85%. The nonwoven fabric is then heat-set at a temperature of 200°C for 45 to 55 seconds to obtain a breathable layer. The hydrophobic fibers are then evenly laid on the upper and lower surfaces of the breathable layer and bonded together to form a nonwoven fabric with a microporous structure.

[0028] Explanation: The hydrophobic treatment of modified fiber a ensures excellent hydrophobic properties on the surface of the nonwoven fabric, effectively preventing water droplet penetration. The web bonding of modified fiber b forms a high-porosity breathable layer, maintaining good air permeability. Hydrophobic fibers are laid on the upper and lower surfaces of the breathable layer, forming a hydrophobic, breathable, and hydrophobic structure. This ensures that water cannot easily penetrate while maintaining the breathability of the nonwoven fabric. Through web bonding, the physical strength and stability of the nonwoven fabric are improved, ensuring durability in various application environments. The 60-85% porosity design not only ensures breathability but also ensures the lightweight and flexibility of the nonwoven fabric.

[0029] Furthermore, the bonding method is hot-press bonding, with a hot-press temperature of 170–240°C, a pressure of 1–3 MPa, and a compaction speed of 10–30 m / min.

[0030] Note: Within a temperature range of 170–240℃, the thermoplastic components in the hot melt adhesive or fibers can fully melt. Combined with a pressure of 1–3 MPa, this ensures a strong bond between the fibers, improving the tensile strength and durability of the nonwoven fabric. A moderate compaction speed ensures sufficient contact and adhesion between the fibers, avoiding insufficient adhesion due to excessive speed, while also preventing over-compaction due to excessive speed, which would affect air permeability. Appropriate temperature and pressure settings result in a smoother nonwoven fabric surface, more uniform fiber distribution, improved hand feel, and enhanced aesthetics of the finished product.

[0031] The beneficial effects of this invention are as follows: PTFE micropowder, i.e., polytetrafluoroethylene, due to its extremely low surface energy and hydrophobic properties, enables nonwoven fabrics to maintain high breathability while effectively blocking the intrusion of water molecules, achieving both breathability and waterproofing. The addition of nano-silica and polyurethane resin significantly improves the mechanical strength and durability of the nonwoven fabric, allowing it to withstand greater physical pressure and wear while maintaining its lightweight characteristics. The addition of antistatic agents reduces the accumulation of static electricity caused by friction during use. Polyester fiber, as the main component, provides the basic structure and cost advantage of the nonwoven fabric, while ensuring the material's flexibility and a certain degree of elasticity. The hydrophobic treatment layer further enhances the waterproof performance of the nonwoven fabric. Hydrophobic treatment before the filaments are bonded together strengthens the hydrophobicity of the nonwoven fabric without affecting its breathability, achieving a balance between high breathability and waterproofing. Attached Figure Description

[0032] Figure 1 These are bar charts showing the water vapor transmission rate tests of samples from Examples 1-3, 16-19 and Comparative Examples 1-3 of the present invention;

[0033] Figure 2 These are bar charts showing the impermeability test results of samples from Examples 1-3, 16-19 and Comparative Examples 1-3 of the present invention. Detailed Implementation

[0034] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.

[0035] Example 1: A highly breathable and hydrophobic nonwoven fabric, by weight percentage, is composed of 12.5% ​​PTFE micro powder, 7.5% nano-silica, 4.5% polyurethane resin, 2% antistatic agent, and the balance polyester fiber extruded into filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 45 mg / m² on the surface of the filaments. 2 ;

[0036] The method for preparing the highly breathable and hydrophobic nonwoven fabric includes the following steps:

[0037] S1, Raw material mixing

[0038] Polyester fiber, PTFE micro powder, nano silica, polyurethane resin and antistatic agent are mixed evenly according to the formula ratio to obtain a mixture; the antistatic agent is antistatic agent ZJ-NW16; the cooling rate in S3 is 6.5℃ and the stretching ratio is 1.75 times;

[0039] S2, Preparation of molten mixture

[0040] The mixture obtained in S1 is fed into a melt extruder, and the temperature is controlled at 240℃ to fully melt the PTFE micro powder and obtain a melt mixture.

[0041] S3, Extrusion Modification Treatment

[0042] The molten mixture obtained in S2 was stretched into fine filaments using an electrospinning device. The filaments were cooled to room temperature and then soaked and washed in deionized water. After drying, the filaments were completely immersed in a lipase solution and stirred for 9 hours. Then, they were thoroughly washed with distilled water and dried to obtain modified fibers. The temperature of the stirring reaction was controlled at 50°C. The lipase solution consisted of 4.5% Novozym 435, 9% ethylene glycol, and the balance being water by mass percentage.

[0043] S4. Preparation of nonwoven fabric

[0044] The modified fibers obtained from S3 were divided into two groups at a mass ratio of 5:2, denoted as modified fiber a and modified fiber b, respectively. Modified fiber a was immersed in a hydrophobic dispersion and stirred for 10 minutes to form a hydrophobic treatment layer on the surface of the modified fiber. After being taken out and dried, hydrophobic fiber was obtained. Modified fiber b was laid in a crisscross pattern using a multi-channel web laying machine, with each layer of fiber web perpendicular to the previous layer. The number of web layers was 13. After all layers were laid, the fiber web was bonded together, retaining a portion of the microporous structure and controlling the porosity at 72%. The nonwoven fabric was then heat-set at a temperature of 200°C for 50 seconds to obtain a breathable layer. The hydrophobic fibers were evenly laid on the upper and lower surfaces of the breathable layer and bonded together to form a nonwoven fabric with a microporous structure. The bonding method was hot-press bonding at a temperature of 205°C, a pressure of 2 MPa, and a compaction speed of 20 m / min.

[0045] The preparation method of the hydrophobic dispersion is as follows: 12.5% ​​calcium carbonate, 15% fly ash, 10% bentonite, 5% silica and the balance fluorinated alkylsilane are ball-milled and mixed, and then water is added to prepare a hydrophobic dispersion with a concentration of 0.5 wt% fluorinated alkylsilane.

[0046] S5, Shaping Process

[0047] The nonwoven fabric described in S4 is subjected to heat setting treatment. The heat setting temperature is controlled at 200℃ and the heat setting time is 50s to obtain a highly breathable and hydrophobic nonwoven fabric.

[0048] Example 2: This example is basically the same as Example 1, except that, by mass percentage, it consists of filaments extruded from 10% PTFE micro powder, 5% nano-silica, 3% polyurethane resin, 1% antistatic agent, and the balance polyester fiber, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 10 mg / m² on the surface of the filaments. 2 .

[0049] Example 3: This example is basically the same as Example 1, except that, by mass percentage, it consists of filaments extruded from 15% PTFE micro powder, 10% nano-silica, 6% polyurethane resin, 3% antistatic agent, and the balance polyester fiber, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 80 mg / m² on the surface of the filaments. 2 .

[0050] Example 4: This example is basically the same as Example 1, except that the mixture obtained in S1 is introduced into a melt extruder and the temperature is controlled at 220°C.

[0051] Example 5: This example is basically the same as Example 1, except that the mixture obtained in S1 is introduced into a melt extruder and the temperature is controlled at 260°C.

[0052] Example 6: This example is basically the same as Example 1, except that the nonwoven fabric described in S4 is subjected to heat setting treatment. The heat setting temperature is controlled at 180°C and the heat setting time is 20s to obtain a highly breathable and hydrophobic nonwoven fabric.

[0053] Example 7: This example is basically the same as Example 1, except that the nonwoven fabric described in S4 is subjected to heat setting treatment. The heat setting temperature is controlled at 220°C and the heat setting time is 80s to obtain a highly breathable and hydrophobic nonwoven fabric.

[0054] Example 8: This example is basically the same as Example 1, except that the cooling rate in S3 is 3°C and the stretching ratio is 1.5 times.

[0055] Example 9: This example is basically the same as Example 1, except that the cooling rate in S3 is 10°C and the stretching ratio is 2 times.

[0056] Example 10: This example is basically the same as Example 1, except that the temperature of the stirring reaction in S3 is controlled at 40°C.

[0057] Example 11: This example is basically the same as Example 1, except that the temperature of the stirring reaction in S3 is controlled at 60°C.

[0058] Example 12: This example is basically the same as Example 1, except that, by mass percentage, the lipase solution in S3 consists of 0.1% Novozym 435, 3% ethylene glycol, and the balance water.

[0059] Example 13: This example is basically the same as Example 1, except that, by mass percentage, the lipase solution in S3 consists of 9% Novozym 435, 15% ethylene glycol and the balance water.

[0060] Example 14: This example is basically the same as Example 1, except that the preparation method of the hydrophobic dispersion in S4 is as follows: 5% calcium carbonate, 10% fly ash, 5% bentonite, 1% silica and the balance fluorinated alkylsilane are ball-milled and mixed, and then water is added to prepare a hydrophobic dispersion with a concentration of 0.1 wt% fluorinated alkylsilane.

[0061] Example 15: This example is basically the same as Example 1, except that the preparation method of the hydrophobic dispersion in S4 is as follows: 20% calcium carbonate, 20% fly ash, 15% bentonite, 10% silica and the balance fluorinated alkylsilane are ball-milled and mixed, and then water is added to prepare a hydrophobic dispersion with a concentration of 1 wt% fluorinated alkylsilane.

[0062] Example 16: This example is basically the same as Example 1, except that modified fiber a is immersed in a hydrophobic dispersion and stirred for 5 minutes to form a hydrophobic treatment layer on the surface of the modified fiber. After being taken out and dried, hydrophobic fiber is obtained. Modified fiber b is web-laid and bonded to obtain a breathable layer with an average porosity of 60-62%. Hydrophobic fiber is evenly laid on the upper and lower surfaces of the breathable layer and bonded to form a nonwoven fabric with a microporous structure.

[0063] Example 17: This example is basically the same as Example 1, except that modified fiber a is immersed in a hydrophobic dispersion and stirred for 15 minutes to form a hydrophobic treatment layer on the surface of the modified fiber. After being taken out and dried, hydrophobic fiber is obtained. Modified fiber b is web-laid and bonded to obtain a breathable layer with an average porosity of 83-85%. Hydrophobic fiber is evenly laid on the upper and lower surfaces of the breathable layer and bonded to form a nonwoven fabric with a microporous structure.

[0064] Example 18: This example is basically the same as Example 1, except that the bonding method is hot-press bonding, the hot-press temperature is 170℃, the pressure is 1MPa, and the compaction speed is 10m / min.

[0065] Example 19: This example is basically the same as Example 1, except that the bonding method is hot-press bonding, the hot-press temperature is 240℃, the pressure is 3MPa, and the compaction speed is 30m / min.

[0066] Comparative Example 1: Referring to Example 1, the filament, by mass percentage, is composed of 20% PTFE micro powder, 15% nano-silica, 8% polyurethane resin, 5% antistatic agent, and the balance polyester fiber extruded into filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 8 mg / m² on the surface of the filaments. 2 .

[0067] Comparative Example 2: Referring to Example 1, the modified fibers were not soaked in a hydrophobic dispersion and were directly hot-pressed to prepare nonwoven fabric.

[0068] Comparative Example 3: Referring to Example 1, when preparing the nonwoven fabric, both modified fiber a and modified fiber b were soaked in a hydrophobic dispersion and then hot-pressed together to form the nonwoven fabric.

[0069] To investigate the properties of the nonwoven fabrics manufactured in Examples 1-3, 16-19, and Comparative Examples 1-3, the main materials were determined according to the experimental formula, and 10 sets of samples were obtained for testing. Figure 1 , 2 The experimental results were obtained using the testing methods specified in JC / T2291 standard. Water impermeability was tested according to GB / T328.10 standard, and water vapor transmission rate was tested according to GB / T17146 standard. The specific investigation is as follows: Water impermeability...

[0070] 1. To investigate the effect of the raw material ratio of highly breathable and hydrophobic nonwoven fabric on the performance of nonwoven fabric samples:

[0071] like Figure 1 , 2 As shown, a comparison of Examples 1 to 3 reveals that Example 1 has the highest water vapor permeability. As the raw material ratio changes, the water vapor barrier properties of the nonwoven fabric change, and Example 3 has the lowest water vapor permeability. Example 1 has the highest water impermeability, while Example 3 has higher water impermeability than Example 2. This indicates that the raw material ratio of the high-permeability and hydrophobic nonwoven fabric has a significant impact on the air permeability and hydrophobicity of the nonwoven fabric samples.

[0072] Comparing Example 1 with Comparative Example 1, it can be seen that the water vapor permeability of Comparative Example 1 is significantly lower than that of Example 1. The air permeability of the raw material ratio of Comparative Example 1 is poor. The formulation of Example 1 achieves a better balance between air permeability and water vapor barrier properties, and is suitable for applications that require both good air permeability and water vapor barrier properties.

[0073] 2. Investigate the influence of nonwoven fabric preparation process parameters on the properties of highly breathable and hydrophobic nonwoven fabric samples:

[0074] like Figure 1 , 2 As shown, a comparison of Examples 16 and 17 reveals that, in terms of water vapor permeation, Example 16 has a value of 1658 g / m³. 2 ×24h, significantly higher than 1287g / m³ in Example 17. 2 ×24h, which means that the material formulation of Example 16 allows more water vapor to pass through compared to Example 17; the impermeability index shows that the value of Example 16 is 117cm H2O, which is much lower than the 151cm H2O of Example 17, indicating that the material of Example 16 is weaker in terms of waterproofness.

[0075] Comparing Examples 16 and 17 with Comparative Example 2, it can be seen that: in terms of water vapor transmission rate, Example 16 has the highest value, while the value of Comparative Example 2 is between that of Example 16 and Example 17. Example 16 is significantly higher than Comparative Example 2 in terms of water vapor transmission rate. In terms of impermeability index, the value of Comparative Example 2 is 102 cm H2O, which is lower than that of Examples 16 and 17, indicating that Comparative Example 2 has the weakest performance in terms of waterproofness.

[0076] 3. Investigate the influence of hot-press bonding process parameters on the properties of highly breathable and hydrophobic nonwoven fabric samples:

[0077] like Figure 1 , 2 As shown, Figure 1 , 2 As shown, a comparison of Examples 18 and 19 reveals that the water vapor permeation rate in Example 18 is 1574 g / m³. 2 ×24h, compared to 1419 g / m² in Example 19 2 The ×24h value is slightly higher, indicating that the process of Example 18 has better air permeability; the water impermeability index shows that the value of Example 18 is 132cm H2O, which is lower than that of Example 19 (148cm H2O), suggesting that the material of Example 19 is superior to that of Example 18 in terms of waterproof performance.

[0078] A comparison of Examples 18 and 19 with Comparative Example 3 shows that, in terms of water vapor permeation, the values ​​of Examples 18 and 19 are both higher than the 1286 g / m³ of Comparative Example 3. 2 After 24 hours, it can be seen that the air permeability of the control example 3 is lower. The water impermeability index shows that the value of the control example 3 is 163 cm H2O, which is higher than that of examples 18 and 19, indicating that the control example 3 has better waterproof performance.

Claims

1. A method for producing a highly breathable and hydrophobic nonwoven fabric, characterized in that, By weight percentage, the raw material of the high-breathability hydrophobic nonwoven fabric consists of 10-15% PTFE micro powder, 5-10% nano silica, 3-6% polyurethane resin, 1-3% antistatic agent, and the balance polyester fiber extruded into filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the hydrophobic treatment layer has a mass coverage of 10-80 mg / m² on the surface of the filaments. The production method of the high air permeability and hydrophobic nonwoven fabric includes the following steps: S1, Raw material mixing Polyester fiber, PTFE micro powder, nano silica, polyurethane resin and antistatic agent are mixed evenly according to the formula ratio to obtain a mixture. S2, Preparation of molten mixture The mixture obtained in S1 is fed into a melt extruder, and the temperature is controlled at 220~260℃ to fully melt the PTFE micro powder and obtain a melt mixture. S3, Extrusion Modification Treatment The molten mixture obtained from S2 was stretched into fine filaments using an electrospinning device. The filaments were cooled to room temperature and then soaked and washed in deionized water. After drying, the filaments were completely immersed in a lipase solution and stirred for 3-15 hours. Then, they were thoroughly washed with distilled water and dried to obtain modified fibers. S4. Preparation of nonwoven fabric The modified fibers obtained from S3 were divided into two groups at a mass ratio of 1 to 4:1, denoted as modified fiber a and modified fiber b, respectively. Modified fiber a was immersed in a hydrophobic dispersion and stirred for 5 to 15 minutes to form a hydrophobic treatment layer on the surface of the modified fiber. After being taken out and dried, hydrophobic fiber was obtained. Modified fiber b was laid in a crisscross pattern using a multi-channel web laying machine, with each layer of fiber web perpendicular to the previous layer. The number of web layers was 6 to 20. After all layers were laid, the fiber web was bonded together, retaining a portion of the microporous structure and controlling the porosity at 60 to 85%. The nonwoven fabric was then heat-set at a temperature of 200°C for 45 to 55 seconds to obtain a breathable layer. The hydrophobic fibers were evenly laid on the upper and lower surfaces of the breathable layer and bonded together to form a nonwoven fabric with a microporous structure. S5, Shaping Process The nonwoven fabric described in S4 is subjected to heat setting treatment, and the heat setting treatment temperature is controlled at 180~220℃ and the heat setting time is 20~80s to obtain a highly breathable and hydrophobic nonwoven fabric. The preparation method of the hydrophobic dispersion described in S4 is as follows: 5-20% calcium carbonate, 10-20% fly ash, 5-15% bentonite, 1-10% silica, and the balance fluorinated alkylsilane are ball-milled and mixed, and then water is added to prepare a hydrophobic dispersion with a concentration of 0.1-1 wt% of fluorinated alkylsilane.

2. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 1, characterized in that, The antistatic agent mentioned in S1 is antistatic agent ZJ-NW16.

3. The method for producing the highly breathable and hydrophobic nonwoven fabric according to claim 1, characterized in that, The temperature of the stirring reaction described in S3 is controlled at 40~60℃.

4. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 1, characterized in that, The lipase solution described in S3, by mass percentage, consists of 0.1-9% Novozym 435, 3-15% ethylene glycol, and the balance being water.

5. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 1, characterized in that, The bonding method is hot-press bonding, with a hot-press temperature of 170~240℃, a pressure of 1~3MPa, and a compaction speed of 10~30m / min.

Citation Information

Patent Citations

  • Preparation method of waterproof and breathable nanofiber membrane

    CN111719245A

  • Antistatic polyester fiber and preparation method thereof

    CN116516513A